Pengaruh Kebiasaan Membaca dan Penguasaan Kosakata Terhadap Kemampuan Membaca Bahasa Inggris - Kurnia Akbar (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
The purpose of this research is to know whether there are the effects of reading habit and vocabulary mastery towards student’s reading skill. The method used was survey. The sample taken was 30 students of Grade XI of Vocational High Schools in Depok using simple random technique. The instrument used to collect the data was a questionnaire. The data analysis used was descriptive statistics such as finding the mean, median, mode, standard deviation, and inferential statistics which was used for finding the simple and multiple correlation coefficients, followed by significance test of correlation coefficient with t test. This research was conducted on April 1 to May 30, 2015. The results showed: 1). There is a significant influence of the reading habit and vocabulary mastery towards student’s reading skill, it was proved by the value of F = 79.250 and f table = 3,35. 2). There is a significant influence between the reading habit towards the student’s reading skill, it was proved by the value of t = 2.319 and Sig. 0.028 < 0.05. 3). There is a significant influence of vocabulary mastery towards student’s reading skill, it was proved by the value of t = 2.608 and Sig. 0.015 < 0.05.